The Effect of Product Attributes, Self-Image, and Social Factors on Purchase Intention of Male Skincare Products - Arif, Ismi Nurul; Nuvriasari, Audita (Economic and Business Horizon, 2025)
The increasing interest of men in personal care highlights the need for companies to understand consumer behavior in the male skincare market. This study aims to examine the influence of product attributes, self-image, and social factors on the purchase intention of male skincare products. A quantitative method with an explanatory approach was employed, involving 100 university students selected through purposive sampling. Data were collected via an online questionnaire using a five-point Likert scale and analyzed through validity and reliability tests, classical assumption tests, and multiple linear regression. The results indicate that product attributes have a positive but non-significant effect on purchase intention, while self-image and social factors have positive and significant effects. The coefficient of determination (R²) of 0.607 shows that these variables explain 60.7% of the variation in purchase intention, with the remaining 39.3% influenced by other factors. These findings suggest that self-image and social factors play a dominant role in shaping purchase intention, implying that marketing and promotional strategies should align with male consumers’ lifestyles and self-perceptions.